COMPREHENSIVE ASSESSMENT OF THE QUALITY OF TWO-LAYER KNITTED FABRICS WITH A NEW STRUCTURE - G. X. Gulyayeva; N. H. Karimova (Bright Mind Publishing, 2025)
The article presents the results of a comprehensive assessment of the quality indicators of double-layer knitted fabrics from spun cotton yarn, using local raw materials effectively. In order to expand the range of knitted fabrics and study the influence of knitting the structure on their shape retention properties and other quality indicators, 7 variants of double-layer knitted fabrics were developed, differing in structure. Samples of double-layer knitted fabrics were produced on a Long Xing LXA 252 SC flatbed knitting machine.
Keywords: Knitwear, structure, wrinkle resistance, abrasion resistance, breathability, penetration.